FRI0276 EARLY TREATMENT WITH ANTI-TNF IS ASSOCIATED WITH HIGHER RESPONSE RATES IN PATIENTS WITH ACTIVE AXSPA. (13th June 2020) - Gulle, S.; Sari, İ. and Durak Ediboglu, E. and Candan, H. and Onen, F. and Akar, S.
Abstract : Background: Treatment options for axial spondyloarthritis (axSpA) is currently limited, and up to 40% of the patients require biologic therapies to control symptoms. Early commencement of biologics suggested to have higher response rates but data regarding this subject is limited. Objectives: The primary aim was to investigate tumor necrosis factor inhibitor (TNFi) response and retention rates in axSpA patients who were treated in the early disease period (symptom duration (≤5 years). Our secondary aim was to identify factors predicting response to TNFi. Methods: Adult axial SpA patients who started TNFi treatments within the five years of their symptoms were identified and defined as "Group 1". Patients whose TNFi treatments started five years after their initial symptoms served as a control group (Group 2: 5-10 years and Group3: ≥10 years). Response and survival rates at 6, 12, and 24 months were calculated. Predictors of response on TNFi survival at 24 months were also analyzed. Results: There was a total of 364 axiSpA (Group 1: 95, Group 2: 82 and Group 3: 187) patients in the study (69.8% male, 46.8±12.6 years). Group 1 patients tended to be younger, with a lower baseline CRP titers and lower HLA–B27 rate compared to the other groups. Drug survival rates were similar between the groups. This finding also remained similar when AS and nraxSpA patients analyzed separately. However, regardless of symptom duration, the drug retention rates were significantly higher in the AS group than in nraxSpA (Table 2). ASAS40 responses were higher in Group 1 than in Group 3 both at 12 and 24 months. Predictors of response based on ASAS40 at 24 months were treatment within the five years of the symptoms (OR:2.2) and age at baseline (OR:0.97) in univariate analysis. However, baseline ASDAS (OR:1.4) was the only factor in multiple regression. Conclusion: In this study we showed the following: 1) TNFi started in the early disease course resulted in a better ASAS40 response at both 12 and 24 months, 2) TNFi timing (started in the early or late disease period) seems not affecting drug retention rates, and 3) baseline disease activity is the most important predictor in achieving ASAS40 response at 24 months. Disclosure of Interests: None declared